Istibdal Wakaf Sebagai Solusi Pendayagunaan Benda Wakaf Masa Post Covid-19: Analisis Pendapat Ulama Mazhab - Tiswarni Tiswarni (Universitas Islam Negeri Raden Fatah Palembang, 2023)
This paper explaines the necessity to maintain the sustainability of the benefits of waqf objects, especially waqf for health facilities through istibdal waqf after the Covid-19 pandemic. When the pandemic hit the country, many people were infected by the corona virus outbreak, thus inspiring several Islamic philanthropic institutions to participate in easing the burden on the society and government by raising waqf funds directed at the procurement of medical devices. After Covid-19 hit, even in some regions, there were calls to lift the